224 Calpainopathy: CAPN compound heterozygosity in a patient with wilson's disease. Issue 12 (14th November 2019) - Wong, Charis; Fletcher, Elaine; Marini-Bettolo, Chiara; Barresi, Rita; Breen, David P
Abstract : A 37 year-old nurse of Czech origin presented with a five year history of progressive, symmetrical limb weakness, myalgia and a tendency to walk on her tip-toes. She had difficulty walking upstairs and lifting her baby. She had a background of Wilson's disease, diagnosed aged 14 on the basis of liver biopsy. Penicillamine-induced myopathy was initially suspected, but symptoms persisted despite switching to trientine. There was no family history of neurological disease. Examination revealed bilateral scapular winging, wasting of upper arms, tightening of Achilles tendons, weakness of neck extensors and proximal limbs (especially biceps), and Gowers' sign. Reflexes and sensation were normal. She had fluctuating hyperCKaemia (1000 – 4000 U/L), and myopathic features on electromyogram and lower limb magnetic resonance imaging. Muscle biopsy showed scattered atrophic fibres without evidence of inflammation. Absence of calpain-3 expression was noted on subsequent review, suggestive of Limb Girdle Muscular Dystrophy type 2a (calpainopathy). The diagnosis was confirmed by genetic testing: she was a compound heterozygote for pathogenic variants in the CAPN3 gene (c.598-612del and c.1381C>T). Management included neurophysiotherapy, genetic counselling, and surveillance of respiratory and cardiac function. In summary, recognising her clinical phenotype was essential in guiding appropriate immunohistology and genetic testing to secure the diagnosis.